Cancer cells with defective RB and CDKN2A are resistant to the apoptotic effects of rapamycin. (1st December 2021) - Chakraborty, Sohag; Utter, Matthew B.; Frias, Maria A.; Foster, David A.
Abstract: Inhibition of mammalian target of rapamycin complex 1 (mTORC1) with rapamycin in the absence of transforming growth factor-β (TGFβ) signaling induces apoptosis in many cancer cell lines. In the presence of TGFβ, rapamycin induces G1 cell cycle arrest; however, in the absence of TGFβ, cells do not arrest in G1 and progress into S-phase where rapamycin is cytotoxic rather than cytostatic. However, we observed that DU145 prostate and NCI–H2228 lung cancer cells were resistant to the cytotoxic effect of rapamycin. Of interest, the rapamycin-resistant DU145 and NCI–H2228 cells have mutations in the RB and CDKN2A tumor suppressor genes. The gene products of RB and CDKN2A (pRb and p14 ARF ) suppress E2F family transcription factors that promote cell cycle progression from G1 into S. Restoration of wild type RB or inhibition of E2F activity in DU145 and NCI–H2228 cells led to rapamycin sensitivity. These data provide evidence that the combination of mutant RB and mutant CDKN2A in cancer cells leads to rapamycin resistance, which has implications for precision medicine approaches to anti-cancer therapies. Highlights: Inhibition of mTORC1 with rapamycin in the absence of TGFβ signaling induces apoptosis in many cancer cell lines. Cancer cells harboring mutations in both RB and CDKn2A are resistant to the apoptotic effects of rapamycin. Restoration of wild type RB or inhibition of E2F family transcription factor activity restored rapamycin sensitivity. These findings have relevance for precision medicine therapeutics involving the targeting of mTORC1-mediated survival signals.